Contact dermatitis on the lower eyelid related to tick infestation: A case report in Taiwan - Lin, Yun-Hsuan (Taiwan J Ophthalmol, 2016)
Tick bite on the lower eyelid is a rare condition. We reported a case of contact dermatitis on the lower eyelid related to the tick infestation. Ticks are vectors for disease transmission. Symptoms and treatments for tick-borne diseases were reviewed.